Seasonal and Inter-annual Variation of Evapotranspiration in Amazonia Based on Precipitation, River Discharge and Gravity Anomaly Data - Sun, Linghui; Baker, Jessica C. A.; Gloor, Emanuel; Spracklen, Dominick; Boesch, Hartmut; Somkuti, Peter; Maeda, Eduardo; Buermann, Wolfgang (Frontiers in Earth Science, 2019)
The large extent of forest in the Amazon recycles vast quantities of precipitation back to the atmosphere, influencing local and regional climate. Although the magnitude of the evapotranspiration (ET) flux has historically been difficult to quantify, here we employ a catchment-balance approach to estimate ET for five Amazon sub-basins and for the whole Amazon basin. Our results suggest a more complex mechanism of control on seasonal ET than has been previously understood. Specifically, we found that maximum ET in wet catchments co-occurs with maximum precipitation and solar radiation through different times in the year, while biotic factors (such as the timing of leaf flush) are an additional influence on ET in drier catchments. In general, intra-annual variation in ET was found to be low, however, inter-annual time series showed a strong negative anomaly in Amazon ET during the 2015/16 El Niño, consistent with previously reported reductions in forest productivity during this event. Overall, our results help to explain the strong carbon cycle response to the 2015/16 El Niño, which saw the Amazon become a net source of CO2 to the atmosphere.